2020
DOI: 10.1038/s41598-020-69769-3
|View full text |Cite
|
Sign up to set email alerts
|

The indirect effect of peer problems on adolescent depression through nucleus accumbens volume alteration

Abstract: Literature suggests that neurobiological factors such as brain structure play an important role in linking social stress with depression in adolescence. We aimed to examine the role of subcortical volumetric alteration in the association between peer problems as one type of social stress and adolescent depression. We hypothesized that there would be indirect effects of peer problems on adolescent depression through subcortical volumetric alteration. Seventy eight adolescents with major depressive disorder (MDD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…The putamen is involved in distinct brain functions - such as learning, cognitive functioning, or reward ( Ghandili and Munakomi, 2020 ) - previous reports from our group have already shown hypertrophy in sensorimotor corticostriatal circuits, which is accompanied by a shift to habit-behavior strategies ( Soares et al, 2012 ). The nucleus accumbens gray matter increases have been linked to anxiety ( Kühn et al, 2011 ; Lee et al, 2020 ), being also identified as a biomarker for treatment-responders ( Burkhouse et al, 2020 ). Nonetheless, the residual effect observed in all these regions, that were not confirmed in our FreeSurfer analysis, preclude any conclusion on relevant associations between the volumes of these brain regions and perceived stress scores.…”
Section: Discussionmentioning
confidence: 99%
“…The putamen is involved in distinct brain functions - such as learning, cognitive functioning, or reward ( Ghandili and Munakomi, 2020 ) - previous reports from our group have already shown hypertrophy in sensorimotor corticostriatal circuits, which is accompanied by a shift to habit-behavior strategies ( Soares et al, 2012 ). The nucleus accumbens gray matter increases have been linked to anxiety ( Kühn et al, 2011 ; Lee et al, 2020 ), being also identified as a biomarker for treatment-responders ( Burkhouse et al, 2020 ). Nonetheless, the residual effect observed in all these regions, that were not confirmed in our FreeSurfer analysis, preclude any conclusion on relevant associations between the volumes of these brain regions and perceived stress scores.…”
Section: Discussionmentioning
confidence: 99%
“…Sex‐specific differences are conceivable given the high density of sex steroid receptors in the nucleus accumbens (Goldstein et al., 2001): In male mammals, stress exposure and stress‐induced anhedonia have been linked to increased spine density, dendritic hypertrophy, and larger volumes of the nucleus accumbens (Bessa et al., 2013; Warren et al., 2014). In human adolescents of both sexes, larger nucleus accumbens volumes have been related to peer problems, but interactions with sex have not been probed (Lee et al., 2020). In a neuroimaging study with women, bilateral ventral striatal activations have been decreased by grieving for an AL (Najib et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic stress has also been related to structural changes in the rat dorsal striatum paralleling a behavioral bias toward habit (Dias‐Ferreira et al., 2009). In human neuroimaging studies, reduced dorsal striatal volumes have been associated with long‐term occupational stress (Blix et al., 2013; Savic, 2015) and early life stress (Cohen et al., 2006), and enlarged nucleus accumbens volumes mediated the link between peer problems and adolescent depression (Lee et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, prefrontal regions develop the most slowly in the brain, and therefore may be sensitive to developmental influences from childhood through early adulthood, 7 when the prefrontal cortex (PFC) is more fully mature (Dahl, 2004;Hensch, 2004;Luby et al, 2019). While we suspect that parenting has a highly influential effect on offspring brain development, we recognize that a range of other intertwined factors, such as socioeconomic status (Whittle et al, 2017), adverse events outside the parent-child relationship (Luby et al, 2019), and other interpersonal factors such as peer relationships (Lee et al, 2020) are likely influential as well.…”
mentioning
confidence: 93%